1998
DOI: 10.1177/096032719801700104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of selenium on vanadium toxicity in different regions of rat brain

Abstract: The protective effect of selenium on the neurotoxicity of vanadium in different brain regions of rats was investigated. The lipid peroxidation was significantly accentuated after intraperitoneal (i.p.) administration of vanadium (1.5 mg kg71 b.wt) for a period of 12 consecutive days to rats. The increase in lipid peroxidation was inhibited by selenium treatment (0.02 mg kg71 b.wt., i.p.) for 12 consecutive days. Vanadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 18 publications
1
31
1
Order By: Relevance
“…A fall in the alkaline phosphatase activity may be attributed to the displacement of Mg 2 + by VO 2 + because its size resembles with Mg 2+ . These findings are substantiated by various authors (Johari et al, 2002;Haider et al, 1998;Nechay, 1984). Inhibition in adenosine triphosphatase pattern is due to the unphosphorylated enzyme which interferes with metal ion.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…A fall in the alkaline phosphatase activity may be attributed to the displacement of Mg 2 + by VO 2 + because its size resembles with Mg 2+ . These findings are substantiated by various authors (Johari et al, 2002;Haider et al, 1998;Nechay, 1984). Inhibition in adenosine triphosphatase pattern is due to the unphosphorylated enzyme which interferes with metal ion.…”
Section: Discussionsupporting
confidence: 74%
“…Selenoproteins are generally known to concentrate in cytosol of animal tissues and have a role in immune response and liver cirrhosis in human body. This protects neuronal cells against neurotoxic effects of vanadium by maintaining the availability of antioxidant nonprotein sulphydryl groups (Haider et al, 1998).The protective mechanism could be attributed due to the competition between selenium and vanadium for binding with the functional proteins and bioligand or active tissue sites or the formation of a reversible compound, metal-selenite thus reducing the availability of "free" concentration of toxic metals ions in the body might be a possible mechanism for the observed antagonism between Vanadium and Se. Thus T+Se was most effective and prevented oxidative degradation of biological membrane by catalyzing the donation of hydrogen atom from reduced glutathione.…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that simultaneous administration of selenium dioxide (0.02 mg Se/kg b.w.) to metavanadate-exposed rats prevented adverse V-induced action (Haider et al 1998). Se was also demonstrated to produce beneficial effects in conjunction with a therapeutic agent, Tiron (Shrivastava et al 2007).…”
Section: Selenium Interactions With Vanadiummentioning
confidence: 95%
“…In the available literature, there are only few reports investigating the biological interactions between Se and V. The in vivo study regarding the effects of selenium dioxide (SeO 2 ) on metavanadate-induced toxicity was performed by Haider et al (1998). The researchers treated rats intraperitoneally with sodium metavanadate (1.5 mg vanadium/kg b.w.)…”
Section: Selenium Interactions With Vanadiummentioning
confidence: 99%
“…Vanadium emission from human industrial activities has been estimated to comprise about 53% of total atmospheric vanadium (Hope 1994). A major source of vanadium toxicity remains the burning of fossil fuels in the Arabian Gulf (Haider et al 1998) and the Niger Delta region of Nigeria (Igado et al 2008) where massive incidental and or intentional burning of vanadium containing fuels results in pollution of confined ecosystems.…”
Section: Introductionmentioning
confidence: 99%